Religious Commitment and Empathic Concern: An Empirical Study of German Youth - Ziebertz, Hans-Georg (Journal of empirical theology, 2018)
There is very extensive literature on whether and how religiosity and empathy are related. Such research shows very different results, with some finding a positive influence while others seeing no influence. This paper presents research conducted on German youth (N=2157) regarding the question of how young people score on empathic concern and which concepts function as predictors. Therefore, different concepts on religious commitment are included, and in order to properly assess the meaning of religiosity in the social context of young people, socio-cultural concepts and socio-demographic characteristics are similarly included. The findings show that around two thirds of the respondents score positive or very positive on empathic concern, and that empathic concern correlates with both religious and socio-cultural concepts. Our regression analysis shows that among religious concepts the centrality of religiosity has the strongest influence (β=.220) and among the socio-religious concepts the students' support for multiculturalism is the strongest factor (β=.195). Admittedly, the beta of sex is even higher, as being female shows the strongest influence on empathic concern (β=.265).